Philosophical Study of The Historical Controversy on The Recruitment of Walisongo - Widiastuti, Widiastuti; Mahmudi, Mahmudi; Bulut, Sefa (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
The majority of Walisongo came from abroad. The background of their arrival in Java gave rise to polemics. The first opinion states that they went to Java by chance. Second opinion is based on information from Kanzul Ulum that they went to Java because they were recruited by the Ottoman government. This research uses the Philosophy of History method, which combines the empirical scientific paradigm and the speculative philosophical paradigm. The results of this research show that both opinions can be linked to cyclical patterns. The difference is that the first opinion tends to be the same as Augustine's version of the Fatum Law, which focuses on the afterlife. Meanwhile, the second opinion tends to be the same as Ibn Khaldun's version of the Fatum Law, which is not only related to the afterlife but also the process of educating humans who fight for their society. The driving factors that give rise to these two opinions can also be related to the hadith that motivate Muslims to preach. If the meaning is linked to Augustine's Fatum Law, then there is no need for recruitment because anyone must be ready to implement it. However, if it is related to Ibn Khaldun's Fatum Law, recruitment is significant in preparing better human resources than before. The ultimate goal of the historical process is its synthesis. The conclusion is that these two opinions are complementary and interrelated because both are part of the cyclical pattern of the spread of Islam in Java since the 13th century. First speculation focuses on the spread of Islam during the Walisongo period in the 15th-16th century, while the second speculation discusses the Walisongo recruitment plan, which has started since the 14th century.